The political dimension of implementing environmental reform: lessons from Costa Rica - Kaimowitz, D.; Segura, O. (1996)
This chapter examines the political and economic factors that explain why certain environmental policy reforms have been more successful in Costa Rica than others. In particular, it looks at why the country has advanced much faster in terms of reducing deforestation and creating national parks than it has in the case of reducing urban air pollution. Reducing hazards associated with agricultural pesticides is presented as an intermediary case. The basic explanation given is that the Costa Rican economy (and power structure) was already moving away from extensive cattle ranching, which made it easier to conserve forests. On the other hand, the general context of structural adjustment and trade liberalization led to a massive influx of used cars, and that was a very popular policy among groups that were able to purchase cars for the first time.